Promotion's impact on digital era reading habits at Kwara State University - Eiriemiokhale, Kennedy Arebamen; Sulaiman, Kabir Alabi (Jurnal Informatio, 2024)
The progress of a country is closely linked to its education system, as educated people are critical to its development. In Nigeria, there's a noticeable decline in reading interest among university students. They seem to prefer less meaningful activities over reading. This study investigates how promoting reading can impact the reading habits of students in the digital age, specifically at Kwara State University's Faculty of Information and Communication Technologies. The research used a survey method to collect data from students across three departments: Computer Science, Mass Communication, and Library and Information Science, totaling 1334 students. A sample of 299 students was chosen using the Raosoft sample size calculator. The survey was conducted using an online questionnaire distributed via social media. Out of 299, only 152 students responded, which is about 51%. The findings revealed that students use various digital tools for reading, including online databases, websites, emails, mobile phones, and videos. The internet makes reading more engaging. Most students read for exams, personal development, academic purposes, entertainment, and research. In conclusion, the study shows that promoting reading positively influences the reading habits of students in the digital era at Kwara State University. This suggests that encouraging reading can effectively enhance students' engagement with reading in today's digital world.